Brucellosis as trigger for autoimmune hepatitis in susceptible individual - Al-Obeidy, Eman Sh. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Autoimmune hepatitis (AIH) is a rare chronic liver disease of unknown etiology, characterized by hypergammaglobulinemia, characteristic autoantibodies, and afavorable response to immunosuppressive treatment. Strong circumstantial evidences denoted that there is quite long list of environmental factors such as (food additives and drugs), viruses and toxins which play an important role in precipitating this disease. Brucellosis is endemic in Iraq. It may involve any organ in the body. Liver is frequently involved. Doxycycline used for treatment occasionally may lead to hepatotoxicity.Objective: the aim of the study is To show the relationship between brucellosis , AIH, and hepatotoxicity of doxycycline .Methods: the study was performed on 2 Iraqi patients with brucellosis, attending the teaching hospital for gastroenterology and liver disease in the period between November2003 and July 2004. Brucella were studied by Rose Bengal test and confirmed by indirect immuno florescence assay (IIF).Results: anti-SLA/LP Abs was detected in 2 patients with brucellosis. Conclusion: brucellosis or doxycycline is a trigger of AIH